2007
DOI: 10.1073/pnas.0703732104
|View full text |Cite
|
Sign up to set email alerts
|

On the ability of the Viking gas chromatograph–mass spectrometer to detect organic matter

Abstract: ] claims to show that the Viking GCMS (gas chromatograph-mass spectrometer) experiment, which carried out a search for organic matter at the surface of Mars in 1976, ''may have been blind to low levels of organics.'' To rebut this assertion, the Viking experiment, test data, and results on Mars are reviewed, and the fallacies in the design, execution, and interpretation of the new experiments presented by Navarro-Gonzalez et al. are critically examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…Through the ages, this bombardment should have enriched the martian soil with organic carbon. Contrary to these expectations, the Viking probes sent to Mars in 1976 found no traces (<1 ppb) of organic molecules in the upper soil, which initiated the controversy about martian soil chemistry (Oyama et al, 1978;Biemann, 1979Biemann, , 2007Huguenin et al, 1979;Hunten, 1979;Oro and Holzer, 1979;Mancinelli, 1989;McDonald et al, 1998;Bullock et al, 1994;Schuerger and Clark, 2008).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Through the ages, this bombardment should have enriched the martian soil with organic carbon. Contrary to these expectations, the Viking probes sent to Mars in 1976 found no traces (<1 ppb) of organic molecules in the upper soil, which initiated the controversy about martian soil chemistry (Oyama et al, 1978;Biemann, 1979Biemann, , 2007Huguenin et al, 1979;Hunten, 1979;Oro and Holzer, 1979;Mancinelli, 1989;McDonald et al, 1998;Bullock et al, 1994;Schuerger and Clark, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…All three of these issues relate to a particular aspect of martian chemistry, which is the photocatalysis by oxide nano-and microparticles present in martian soil. We suggest that photocatalytically active iron(III) oxides can be the elusive ''oxidizer'' responsible for the degradation of the organic component of the regolith (Biemann, 1979;Zent and McKay, 1994;Benner et al, 2000;Biemann, 2007). Furthermore, the photooxidation of acetates (currently thought to be the terminal product of stepwise oxidation of the aliphatic component of meteoritic kerogen, see Benner et al, 2000) that release methyl radicals could be responsible for abiogenic methane production on Mars.…”
Section: Introductionmentioning
confidence: 95%
“…An instrument analogous to SAM flew on the Viking mission and did not detect organics via pyrolytic analysis. All evidence suggests that the Viking technical approach and instrument worked according to its design (Biemann, 1979, Biemann, 2007 so these Viking results do not exclude the potential presence of abundant IOM, if the IOM was derived predominantly from OCs. IOM in OCs has already been subjected to extensive natural pyrolysis in the OC parent body (Cody et al, 2008).…”
Section: Interstellar Organic Mattermentioning
confidence: 99%
“…A series of studies (Navarro-González et al, 2006, 2011NavarroGonzalez and McKay, 2011) suggested that the presence of perchlorate and other oxidants in the martian regolith renders the Viking results difficult to interpret because of the high probability of either oxidizing or chlorinating indigenous organic molecules during heating. These observations have been contested (Biemann, 2007). As a result of these complications, the Panel did not rely on the earlier non-detections of organics in Mars regolith.…”
Section: Considerations Related To Specific Contaminantsmentioning
confidence: 99%